2018
DOI: 10.1111/nyas.13632
|View full text |Cite
|
Sign up to set email alerts
|

Control of the inflammatory response during pregnancy: potential role of VIP as a regulatory peptide

Abstract: A network of cell-cell communications through contact and soluble factors supports the maternal-placental interaction and provides a suitable environment for fetal growth. Trophoblast cells take center stage at these loops: they interact with maternal leukocytes to sustain the varying demands of gestation, and they synthesize hormones, cytokines among other factors that contribute to the maintenance of immune homeostasis. Here, we discuss vasoactive intestinal peptide (VIP) and its potential as a regulatory ne… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
19
0
1

Year Published

2019
2019
2023
2023

Publication Types

Select...
5
2

Relationship

1
6

Authors

Journals

citations
Cited by 26 publications
(20 citation statements)
references
References 61 publications
0
19
0
1
Order By: Relevance
“…Originally described as a neuropeptide, VIP has emerged as a very interesting regulatory factor at the feto-maternal interface [27,81]. In human pregnancy, VIP is expressed by the syncytiotrophoblast directly at the site of fetomaternal interaction, highly suggestive of a crucial role in regulating the maternal immune response [81].…”
Section: Vip -Potent New Kid On the Blockmentioning
confidence: 99%
See 3 more Smart Citations
“…Originally described as a neuropeptide, VIP has emerged as a very interesting regulatory factor at the feto-maternal interface [27,81]. In human pregnancy, VIP is expressed by the syncytiotrophoblast directly at the site of fetomaternal interaction, highly suggestive of a crucial role in regulating the maternal immune response [81].…”
Section: Vip -Potent New Kid On the Blockmentioning
confidence: 99%
“…While an essential function of these hormones is to regulate maternal metabolism in order to promote fetal growth or alter the ability of fetal trophoblast cells to invade maternal tissue, several of these factors have been shown to possess additional immune modulatory capacity [25,26]. hCG is produced by the syncytiotrophoblast, the single layer of contiguous fetal tissue directly in contact with the maternal circulation, while VIP is produced by the underlying cytotrophoblast tissue [27]. hCG is produced by the syncytiotrophoblast, the single layer of contiguous fetal tissue directly in contact with the maternal circulation, while VIP is produced by the underlying cytotrophoblast tissue [27].…”
Section: Hormone Regulation Of the Reproductive Cycle -Introducing Thmentioning
confidence: 99%
See 2 more Smart Citations
“…It has been extensively demonstrated that endometrial and trophoblastic cells contribute to the maintenance of immune homeostasis through soluble and contact factors during pregnancy (3,(14)(15)(16)(17). One of the factors proposed to have an immunoregulatory role during implantation and at the early maternal-fetal interface is vasoactive intestinal peptide (VIP) (18,19). VIP is produced by stromal cells (20), syncytium, and cytotrophoblastic cells in the first and third trimesters (21) by extravillous trophoblast (EVT) cells and decidual glandular cells (22,23).…”
Section: Introductionmentioning
confidence: 99%